Legal Politics of Legislation of Regional Regulations in Indonesia - Asnawi, Eddy (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
Regional regulations are written regulations containing generally binding legal norms established by the Regional People's Representative Council with the joint approval of the Regional Head. The regional legislation program has an important and strategic position in the formation of regional regulations. However, most local regulations actually get rejection from the community until they are revoked by the government. The method used in this research is normative legal research. The process of making local regulations rarely involves the community so that local regulations that are born are often not accepted by the community. The Regional Government and the Regional People's Legislative Assembly should first prepare a regional legislation program to determine the needs of the region and the needs of the community, then make regional regulations that are in accordance with the Regional Medium-Term Development Plan or Regional Strategic Plan. Therefore, there must be political will from the Regional Government and the Regional House of Representatives to establish cooperation with universities in conducting studies on a problem so that it becomes an academic text that is ready to be ratified into a regional regulation.